Influential Article Review - A Conceptual Design of the Innovation Process - Sharp, Vanessa; Robbins, Melody; Martinez, Valerie (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: This paper introduces the evolving understanding and conceptualization of innovation process models. We categorize the different approaches to understand and model innovation processes into two types. First, the so-called innovation management approach focuses on the evolution of corporate innovation management strategies in different social and economic environments. The second type is the conceptual approach which analyses the evolution of innovation models themselves as well as the models’ theoretical backgrounds and requirements. The focus in this second approach is the advantages and disadvantages of different innovation models in how far they can describe the reality of innovation processes. The paper focuses on the advantages and disadvantages as well as the potential and limitations of the approaches. It also proposes potential future developments of innovation models as well as the analysis of the driving forces that underlie the evolution of innovation models. The article concludes that the predominant open innovation paradigm requires rethinking and further development towards an ‘active innovation’ paradigm. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.